The Synergy of Islamic Religious Education Learning and Religious Culture in Revitalizing Character Education at MTs Nurul Islam Musuk Boyolali - Ayu Agustina Eka Putri; Mutohharun Jinan (Journal of General Education and Humanities, 2026)
The central issue examined in this study is the decline in students' character, reflected in the weakening of moral standards, religious values, and social responsibility. This condition demands an educational approach that not only emphasizes cognitive development but also addresses affective and behavioral aspects. This study aims to describe the efforts to internalize the values of Islamic Religious Education (IRE), the implementation of religious culture, and the synergy between the two as a strategy to revitalize character education at MTs Nurul Islam Musuk. This research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. The findings indicate that: (1) the internalization of IRE values is conducted through the integration of values in learning, encompassing moral knowing, moral feeling, and moral action; (2) the implementation of religious culture through activities such as Qur'an recitation, congregational prayers, and teacher role modeling creates a supportive school environment for character formation; and (3) the synergy between IRE learning and religious culture is realized through the integration of theoretical instruction in the classroom with real-life practices in the school environment that are persuasive and humanistic. This synergy has proven effective in revitalizing character education, as Islamic values are not only understood conceptually but are also internalized and practiced in students' daily lives.